THE EFFECT OF GRATITUDE TRAINING ON ACADEMIC SELF-EFFICACY IN STUDENTS - Nia Octavia; Wahyu Surya Setiyani; Sevilla Anbar Rachmah; Nerinda Julita Rina; Vioni Alviasti; Sendi Kurnia Wahyu Dinata (Taqrib : Journal of Islamic Studies and Education, 2023)
This study aims to find out and see empirically the effect of gratitude training on the academic self-efficacy of students, especially students of the Faculty of Psychology UIN Raden Fatah Palembang, as well as to find out the differences in academic self-efficacy of students of the Faculty of Islamic Psychology who received gratitude training and who did not get this. The research method in this study uses experiments, using randomization sampling techniques of subjects into experimental and control groups after pretesting. The subject of this study is a student of the Faculty of Psychology UIN Raden Fatah Palembang class of 2020. Design This research is a Randomized Pre-post Test Control Group design. The statistical analysis technique is an independent sample t-test hypothesis test. The results showed that the provision of positive thinking training influenced students' academic self-efficacy, this was based on an independent sample t-test which showed that between the experimental and control groups before the treatment showed no significant differences (p = 0.019 > 005 and the < ttabel value of 2.406, DF = 58.364). However, after being given treatment there was a significant difference where ttabel = 2.406 and p = 0.19 < 0.05. Thus, positive thinking can be one way to improve academic self-efficacy in students.